(3GdeQTOs - (3CHh HcQ eMeO Hf RcQjG GdQGRis; (3GHbQGW GdMcjes
(3ChdgG (B:s
(3OYGfi eG hLOJ Ydjg aUhd ef GdENJdGW hYOe GdfXGe , hGdZehV hGdJbUjQ Yf PcQ LhGeY GdUfGYI cdgG Ch LdgG dci jchf eONdkG Edi GdUfGYI , hWQjbkG ddeJYdejf s
(3BNQgG (B:s
(3hajeG PcQfG hCQTOfG Edjg dhGgH GdYbd GdMeO HdG fgGjI ceG gh Cgd heSJMbg Je GdcJGH hGdMeO ddg hGdUdGg Ydi eMeO hBdg CLeYjf s
(3fSNI KGfjIs
(3GdMHQ HGgJ ai HYV GdUaMGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B229 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
Keywords: (3GdWHs